Brassinosteroids cause cell cycle arrest and apoptosis of human breast cancer cells - Steigerová, Jana; Oklešťková, Jana; Levková, Monika; Rárová, Lucie; Kolář, Zdeněk; Strnad, Miroslav (Chemico-biological interactions, 2010)
Brassinosteroids (BRs) are plant hormones that appear to be ubiquitous in both lower and higher plants. Recently, we published the first evidence that some natural BRs induce cell growth inhibitory responses in several human cancer cell lines without affecting normal non-tumor cell growth (BJ fibroblasts). The aim of the study presented here was to examine the mechanism of the antiproliferative activity of the natural BRs 28-homocastasterone (28-homoCS) and 24-epibrassinolide (24-epiBL) in human hormone-sensitive and -insensitive (MCF-7 and MDA-MB-468, respectively) breast cancer cell lines. The effects of 6, 12 and 24h treatments with 28-homoCS and 24-epiBL on cancer cells were surveyed using flow cytometry, Western blotting, TUNEL assays and immunofluorescence analyses. The studied BRs inhibited cell growth and induced blocks in the G(1) cell cycle phase. ER-α immunoreactivity was uniformly present in the nuclei of control MCF-7 cells, while cytoplasmic speckles of ER-α immunofluorescence appeared in BR-treated cells (IC(50), 24h). ER-β was relocated to the nuclei following 28-homoCS treatment and found predominantly at the periphery of the nuclei in 24-epiBL-treated cells after 24h of treatment. These changes were also accompanied by down-regulation of the ERs following BR treatment. In addition, BR application to breast cancer cells resulted in G(1) phase arrest. Furthermore, TUNEL staining and double staining with propidium iodide and acridine orange demonstrated the BR-mediated induction of apoptosis in both cell lines, although changes in the expression of apoptosis-related proteins were modulated differently by the BRs in each cell line. The studied BRs seem to exert potent growth inhibitory effects via interactions with the cell cycle machinery, and they could be highly valuable leads for agents for managing breast cancer.
Keywords: Receptors, Estrogen; regulace genové exprese u nádorů; nádory prsu; apoptóza; Cell Line, Tumor; Apoptosis; Cell Cycle; Brassinosteroids; Gene Expression Regulation, Neoplastic; lidé; Protein Transport; Breast Neoplasms; cholestanoly; signální transdukce; receptory pro estrogeny; Cholestanones; Signal Transduction; steroidy heterocyklické; buněčný cyklus; transport proteinů; Cholestanols; Cell Cycle Proteins; Steroids, Heterocyclic; cholestanony; proteiny buněčného cyklu; nádorové buněčné linie; brassinosteroidy; Humans